Postmaterialism and Political Elites: The Value Priorities of Brazilian Federal Legislators. Issue 1 (April 2016) - Gatto, Malu A. C.; Power, Timothy J.
We examine the distribution and consequences of postmaterialist value orientations among national legislators in Brazil. Using data collected in the Brazilian Legislative Survey in 2013, we undertake the first systematic study of postmaterialism within the National Congress and the party system and map the materialist/postmaterialist scale onto other salient divisions within the political class. We present five main findings. First, political elites evince vastly higher commitment to postmaterialism than the mass public. Second, Brazilian political elites drawn from constituencies with higher human development are more postmaterialist than their counterparts in other constituencies. Third, within the political class, the materialist/post-materialist cleavage overlaps in important ways with the left–right cleavage. Fourth, although postmaterialism successfully predicts elite attitudes on a number of "new politics" issues that are unrelated to the construction of the postmaterialist scale itself, postmaterialism is a poor predictor of voting behavior on the Congressional floor. Fifth, as others before us, we find institutional factors to be better predictors of legislative voting behavior in the Brazilian context.